Análise da Proposta do Orçamento do Estado 2021 - Mussagy, Ibraimo H. (Observatório do Meio Rural, 2021)
A actual Proposta do Orçamento do Estado (POE) 2021 é a segunda para o quinquénio 2020-2024 e foi elaborada num contexto de transformações económicas e sociais impostas por um novo “normal” provocado pela pandemia da COVID-19, que resultou na maior recessão mundial estimada em cerca de -4.9% para 2020. Essa recessão foi causada pelas medidas de contenção que resultaram na paralisação da actividade económica em grande parte das economias. Em linha com as actuais tendências da economia mundial, a economia Moçambicana também tem registado uma desaceleração (parágrafo 2 da POE 2021). Este texto tem a finalidade de analisar a POE 2021, tendo em conta este contexto. Para tal, a análise foi feita com base nos seguintes documentos: Plano Económico e Social (PES) 2021, POE 2021, mapas integrantes¹, leis orçamentais anteriores e os Relatórios de Execução Orçamental (REO) recentes. Faz-se a articulação destes documentos para se poder perceber a evolução das componentes da POE 2021. O texto compreende três secções, nomeadamente a introdução, a análise do orçamento, onde, de forma específica, o texto analisa os pressupostos macroeconómicos subjacentes à proposta, a evolução das receitas e das despesas, faz uma discussão sobre o défice orçamental, destaca os orçamentos sectoriais com enfase para agricultura, onde o projecto SUSTENTA prevalece em grande parte da discussão, aborda a questão da descentralização e discute o endividamento público, e, na última secção, apresenta-se o resumo das constatações.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; budget / orçamento; decentralization / descentralização; education / educação; health / saúde

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Saúde Para O Povo? Para Um Entendimento Da Economia Política E Das Dinâmicas Da Descentralização No Sector Da Saúde Em Moçambique - Weimer, Bernhard (Moçambique: Descentralizar o Centralismo? Economia Política, Recursos E Resultados, 2012)
Houve em 2011 três acontecimentos que revelaram as dimensões dos desafios que se colocam à gestão do Sistema Nacional de Saúde moçambicano em geral e ao Ministério de Saúde (MISAU) em particular. O primeiro foi uma auditoria externa das contas de 2009 do PROSAUDE II e do Fundo Global, realizada pela empresa de auditoria KPMG e entregue ao governo e aos seus parceiros internacionais em Junho de 2011. Esta auditoria revelou fraquezas consideráveis, nomeadamente em relação à auditoria interna e uma substancial diferença final não reconciliada entre os valores recebidos e os pagamentos efectuados. O segundo foi a crise de abastecimento de medicamentos, amplamente divulgada dos produtos farmacêuticos, quando os meios de comunicação noticiaram, num período de Março a Julho, que, no armazém farmacêutico central do MISAU, o CMAM,49 em Maputo, havia medicamentos no valor de pelo menos 2 milhões de USD que estavam fora de prazo; que os medicamentos se tinham esgotado nos hospitais públicos na Zambézia; e que grandes quantidades de medicamentos tinham desaparecido da farmácia do Hospital Central de Nampula.50 Os doadores recusaram um pedido de um montante adicional de 25 milhões de dólares para reabastecimento de medicamentos, feito pelo Ministro da Saúde em Março de 2011, argumentando que o governo teria que abordar e resolver as questões pendentes dos resultados da auditoria de 2009, antes de os doadores do PROSAUDE assumirem quaisquer compromissos de financiamento adicionais.51 Em terceiro lugar, pouco antes do fim do ano, o pessoal da saúde na Cidade de Nampula, incluindo os médicos, ameaçaram fazer greve, se não lhes fossem pagos os salários, três meses atrasados. Estes acontecimentos põem em relevo, em síntese, alguns dos principais desafios com que a gestão do sector da saúde se debate em Moçambique. Não se sabe até que ponto estes acontecimentos e o que eles revelam sobre a gestão de recursos no sector da saúde afectaram o funcionamento das unidades de saúde nas províncias e distritos, e o impacto sobre a saúde das pessoas doentes e da população em geral. Estas unidades dependem crucialmente de recursos (pessoal, financiamento e medicamentos) para o cumprimento da sua missão de controlar a doença e salvar vidas humanas, ou seja, para produzir os resultados de saúde que lhes compete alcançar, muitas vezes medidos com o indicador DALY.52 Neste artigo, não tentaremos avaliar o impacto das práticas de gestão no sector da saúde e os seus resultados em termos de vidas humanas. Tentaremos antes entender as dinâmicas políticas, económicas e institucionais que influenciam os resultados de saúde e o desempenho das unidades de saúde ao nível subnacional em Moçambique. O nosso argumento é que estas variáveis são determinadas não apenas por factores endógenos ao sector de saúde, como sejam as suas políticas e quadro regulamentar, a sua estrutura institucional, o grau de descentralização, e ainda os recursos que lhe são atribuídos e as suas capacidades de gestão. Também há factoresexógenos, como as decisões orçamentais do Ministério das Finanças, a Ajuda ao Desenvolvimento da Saúde (ADS)53 por parte dos doadores e as suas políticas e mecanismos de atribuição de fundos, como a abordagem sectorial integrada (SWAp)54 e o financiamento conjunto, bem como a mudança social e económica e as formas de governar um país, que produzem impactos decisivos no sistema de saúde e nos seus resultados. No que diz respeito à temática da descentralização da saúde, partimos, em primeiro lugar, do princípio que os ‘objectivos gerais da descentralização e a abordagem sectorial não são incompatíveis’, uma vez que tanto os primeiros como a segunda ‘têm por objectivo aumentar a eficiência técnica; incentivam uma maior participação; e põem a tónica na transparência e prestação de contas’ (Hutton, 2002: 3. Original em inglês). Em segundo lugar, chamamos a atenção para a necessidade de reconhecer um papel forte e normativo do Estado central nas políticas de saúde, na sua gestão, supervisão e questões de equilíbrio social, especialmente em matéria de cuidados de saúde primários, uma vez que a descentralização pode levar à diferenciação e à diversidade e não ao reforço da justiça social nos padrões e no acesso às unidades de saúde (Collins & Green, 1994). Como Booth sugeriu, o papel do Estado central é fundamental, nomeadamente em institucionalizar e supervisionar, do topo para a base, a disciplina de desempenho eficaz na componente de recursos humanos e na produção de serviços de qualidade a nível local (Booth, 2010: 34). Para este artigo, optámos por usar um quadro da análise político-económica para examinar alguns dos determinantes endógenos e exógenos. Do ponto de vista conceptual, a análise da economia política e da descentralização no sector da saúde pode ser estruturada de várias maneiras. Uma, é analisando as mudanças de epidemiologia, de características biomédicas dos corpos humanos e de ocorrênciaschave nos ciclos da vida humana (por exemplo, a fertilidade, a morbilidade ou mortalidade) como resultantes de intervenções por parte das instituições do sector da saúde, em condições sociais, económicas, ambientais e culturais em mudança. Esta abordagem é muitas vezes centrada na pobreza e assenta no pressuposto de que as mudanças institucionais, como a descentralização da prestação de serviços de saúde, conduzem a um aumento do bem-estar e a uma melhoria da saúde nas sociedades, se as intervenções institucionais (planos, programas, prestadores de serviços, etc.) forem ‘correctos’ e dispuserem de suficientes recursos financeiros e humanos, e capacidades, bem como de um quadro adequado de políticas. Dessa forma, julga-se que as taxas de fertilidade e mortalidade acabarão por diminuir, que as doenças infecciosas serão controladas e podem ser alcançados outros progressos no combate à pobreza e à doença (O’ Laughlin, 2010: 7).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; health / saúde

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ------- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - Weimer, Bernhard; Cumbi, Amelia J.; Macuane, José Jaime (MAP Consult, 2012)
The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; health / saúde

Abastecimento De Água Nas Zonas Rurais: Avaliação Dos Progressos Para a Prestação De Serviços Sustentáveis - Munguambe, Carlos Gideon José; Jesus, Vitória Afonso Langa de (IRC International Water and Sanitation Centre, 2011)
This study presents an analytical ‘picture’ of the rural water sub-sector in Mozambique, describing the legal framework, mechanisms for coordination, harmonisation, funding, accountability, participation and supervision. The study was commissioned for the Sustainable Services at Scale, or Triple-S, initiative, which aims to contribute to improving the sustainability of global rural water supply. According to the general population census carried out in 2007, Mozambique had a total population of 20,226,296, 70.2% of whom live in rural areas, with a water coverage rate of only 54%.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; health - WASH / saúde - água, higiene e saneamento; health / saúde